Simultaneous detection and quantification of different biogenic amines (Bangladesh Journal of Pharmacology, 2022)
Biogenic amines are a group of low molecular weight nitrogenous organic compounds that have an important physiological role in cell proliferation, differentiation, and signal transduction. Also, certain biogenic amines act as an important biomarker for the detection of neuroendocrine and cardiovascular disorders in humans. Besides this, the abundance of biogenic amines in food is recognized as a toxin and anti-nutritional element that have several health implications. This visual experiment demonstrates all the critical steps required for the extraction of biogenic amines followed by derivatization and high performance liquid chromatography analysis for the successive detection and quantification of biogenic amines such as histamine, cadaverine, tryptamine, agmatine, putrescine, 2-phenylethylamine, spermine, tyramine, and spermidine.